A Cognitive Look at the "Invisibility" of Older Gay Men Within the Categories 'Gay Man' and 'Elderly Man'. (March 2023) - Coladonato, Rosandra; Carnaghi, Andrea; Ciosk, Mary Ann; Bianchi, Mauro; Piccoli, Valentina
Two studies analyzed whether, at the cognitive level, 'Elderly gay man' is "invisible" both when processing the labels 'Gay man' and 'Elderly man'. We suggest that 'Gay man' is conflated with 'Young man', and that 'Elderly man' is conflated with 'Heterosexual man'. Contact with elderly gay men did not alter the perception of 'Gay man' as prevalently young but weakened the perception of 'Elderly man' as heterosexual by default.